Fundamental elements for infant’s verbal operant acquisition: behavioral analysis of joint attention (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
Language behavioral study presupposes to consider the operant contingencies for the responding repertoire acquisition to stimulus relation such as is proposed for any others behaviors. One of the challenges for the advancements of the verbal behavior Skinner’s proposal is the search of explanations for the description of the essential components in the acquisition and maintenance of the infants’ verbal repertoire. To surpass such a challenge teases, between other things, it is important to invest in the interphrase between verbal operant behavioral conception with other areas of the knowledge, like Developmental Psychology. The present work proposes that a joint attention operant analysis would fulfill paper of basic element for the infants’ verbal operant acquisition, specifically mands and tacts. This examination seems fruitful for the analysis of the impact of Verbal Behavior aspects in teorical explanation and for empirical investigations of the language acquisition essencial components.